The role of guaiacyl moiety in free radical scavenging by 3, 5-dihydroxy-4-methoxybenzyl alcohol: thermodynamics of 3H+/3e− mechanisms. (17th January 2019) - Amić, Ana; Marković, Zoran; Dimitrić Marković, Jasmina M.; Milenković, Dejan; Lučić, Bono
ABSTRACT: Participation of guaiacyl moiety of 3, 5-dihydroxy-4-methoxybenzyl alcohol (DHMBA) in inactivation of free radicals was investigated using the DFT method. The thermodynamics of triple (3H + /3e − ) free radical scavenging mechanisms was investigated. The Gibbs free energies of reactions of inactivation of selected 10 free radicals indicate DHMBA as a potent scavenger. Obtained results allow us to suggest that the contribution of guaiacyl moiety to antioxidant activity of phenolic compounds should be taken into account, what has been scarcely considered until now. GRAPHICAL ABSTRACT: